Pharmacoeconomics of ruxolitinib therapy in patients with myelofibrosis. (2nd April 2016) - Vandewalle, Björn; Andreozzi, Valeska; Almeida, João; Félix, Jorge
Abstract: Background: Overall survival (OS) and other important clinical trial end-points seem increasingly more elusive in supporting rapid and efficient incorporation of innovative cancer drugs in clinical practice. This study proposes a clinical trial based pharmacoeconomic framework to assess the therapeutic and economic value of ruxolitinib in patients with intermediate-2 or high-risk myelofibrosis. Methods: Individual patient level 144 week follow-up data from the COMFORT-II trial was used to account for the crossover effect on overall survival. Lifetime treatment benefits and costs were estimated considering detailed patterns of both ruxolitinib dose adjustments and blood transfusion needs. Results: The authors estimate a 3.3 years increment in life expectancy (HR = 0.30; 95% CI = 0.17–0.55; p -value <0.001) and an incremental cost-effectiveness ratio of €40, 000 per life year gained with the use of ruxolitinib. Conclusion: This study also demonstrates how valuable information from clinical trials can be used to support informed decisions about the early incorporation of innovative drugs.